Strict forest protection: A meaningful contribution to Climate-Smart Forestry? An evaluation of temporal trends in the carbon balance of unmanaged forests in Germany - Nagel, Rouven; Meyer, Peter; Blaschke, Markus; Feldmann, Eike (Frontiers in Forests and Global Change, 2023)
The role of unmanaged forests is discussed controversially in the context of climate change. One of the key questions is, whether they can contribute to the mitigation of climate change as a carbon sink and storage. However, carbon dynamics of forests after the cessation of management are not well understood. We analyzed a set of 64 forest sites, covering wide gradients of time since abandonment (0 – 68 yr.) and stand age (65 – 261 yr.) in even-aged, unmanaged beech forests. Five sites that were unmanaged for >100 years complemented the main dataset. We compiled site-specific carbon balances, distinguishing six carbon-compartments: Carbon in aboveground living and dead biomass, carbon in belowground living and dead biomass, and carbon in the organic layer and the mineral topsoil (0-30 cm). We found positive effects of increasing TSA on the carbon stock in living biomass and aboveground dead biomass for up to 50 years after management ceased. The average increase of the total carbon stock over 50 years of TSA was ≈ 80 Mg C ha-1. The effect of stand age on aboveground living biomass showed a convex relation. Aboveground dead biomass increased logistically with TSA, while belowground dead biomass decreased. On average, the five sites unmanaged for >100 years held lower total carbon stocks compared to the observed biomass peak around 50 years of TSA. However, they contained considerably higher amounts of deadwood. Carbon in the mineral soil did neither change with TSA nor with stand age and was driven by pH. Carbon stocks in newly unmanaged forests increased almost linearly for approximately 50 years after cessation of management. Subsequently, a stabilization or medium-term decrease in carbon stock was observed, likely due to the initiating transition from even-aged to multi-aged structures. We conclude that, besides their value for biodiversity and ecosystem functions, the potential of naturally developing forests as a medium-term carbon sink and long-term stable carbon storage should be considered as a valuable contribution to climate smart forestry.